When Engagement Backfires: Gamification Susceptibility to Financial Misinformation - Dwi Cahyaningdyah; Andhi Wijayanto; Kris Brantas Abiprayu; Syam Widia; Erisa Aprilia Wicaksari (Management Analysis Journal, 2025)
This paper examines five theoretically motivated predictors of susceptibility: gamified financial literacy engagement, subjective financial literacy, emotion regulation, information framing preferences, and cognitive ability. These predictors are embedded within a dual process framework and tested using OLS regression with heteroscedasticity-consistent standard errors on survey data from N = 89 university-affiliated respondents in Indonesia. Two unexpected findings are reported. First, engagement with gamified financial literacy programs is positively and significantly associated with susceptibility, contrary to the hypothesized direction, interpreted as a gamification engagement-without-depth effect consistent with self-determination theory and the Dunning-Kruger literature on overconfidence. Second, information framing preferences are also positively associated, reflecting a ceiling effect and a loss-sensitivity dimension linked to financial anxiety. Financial literacy is negatively associated at a marginal level, while females are less susceptible than males. Objective financial knowledge shows near-zero predictive power, suggesting factual knowledge does not reduce susceptibility. Implications for financial education, consumer protection, and measurement are discussed.